Local Wisdom-Based Learning for Future Chemistry Education Research: A Bibliometric Analysis Using VOSviewer and RStudio Applications - Novia, Khairani; Aznam, Nurfina (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2026)
Since 2015, research on local wisdom in science education has shown consistent growth, with a notable surge in 2023. While studies integrating local wisdom into physics, biology, and mathematics are abundant, bibliometric analyses focusing on chemistry education remain limited. This study aims to map research trends using data from the Web of Science database, which has been analyzed using VOSviewer and RStudio. The results reveal fluctuations in publication trends from 2015 to 2024, with Indonesia among the top 10 contributor countries. Indonesia’s cultural and geographical diversity—spanning multiple islands and ethnic groups—makes it a rich source for local wisdom-based educational research. Education Sciences, a journal based in Switzerland, is the most active publisher, with 26 related articles. Frequently used keywords include learning models, performance, engagement, achievement, pedagogy, and knowledge. Despite increasing interest, Indigenous knowledge remains underexplored in chemistry education. Therefore, integrating local wisdom requires a thoughtful selection of pedagogical strategies, learning content, and relevant chemistry concepts. The findings underscore that this remains a promising area of research that warrants further investigation.